PHYTOCHEMICAL SCREENING AND ANTIMICROBIAL ACTIVITY OF CEROPEGIA JUNCEA ROXB. – A RARE MEDICINAL PLANT: Pharmaceutical Science-Pharmacognosy - P. BOOMIBALAGAN; S. ESWARAN; S. RATHINAVEL (International Journal of Life Science and Pharma Research, 2022)
The phytochemical compounds and antimicrobial activity of different solvent extracts of Ceropegia juncea Roxb. were screened. The qualitative analysis of crude extracts revealed the presence of alkaloids in all solvent extracts. There was a resemblance in occurrence of saponin and steroids in methanol and aqueous extracts, but phenolic compounds and tannins were found common in the extracts prepared with ethyl acetate, chloroform and water. The crude extracts exhibited MIC values ranging between 20 and 80 mg/ml. However, it was observed that extracts at 40-60 mg/ml were found to be MIC for most of the test microorganisms in this study. The antimicrobial observations exemplified significant inhibitory effect of methanolic extract against Pseudomonas aeruginosa, Escherichia coli and Klebsiella pneumonia and aqueous extract for Klebsiella pneumoniae and Proteus vulgaris as compared to positive control amikacin. The results provide baseline information for the use of the solvent extracts of Ceropegia juncea to treat various oral infections caused by bacterial pathogens.